Assessment of Caregiver Knowledge Related to the Physiological Changes and Health Problems in Government Geriatric Home at Baghdad City - Shatha Ahmed M.A.1 , Muna Abdul Kadhum Zeidan2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Population aging can lead to a larger number of individuals with physical and emotional disorders, which increase demand for caregivers, there is a high prevalence of functional disability in older adults and a variability between the genders, with a 42.8% rate among women and 39.6% among men. A quasi experimental study, Analytical, cross-sectional, non-probability convenient study done with sampling of 20 caregivers was conducted in the Geriatric Care Home in Baghdad City (the governmental geriatric home) for the period from 12th of October 2018 to 20th of January 2019 to ass their knowledge about physiological changes and health problems. A questionnaire was used to collect caregiver’s data which consist of two parts: The first part is concerned general information of the study Geriatrichome, and the second part involves two domains involving items concerning caregiver’s knowledge about physiological changes and health problems and their knowledge about emergency care for elderly persons. Results: the study presents that a high percentage (60%) of the study sample was nurses as caregivers in AL- Rashad Geriatric Care Home and (80%) of the study sample are males, (60%) of the caregivers were graduated from college in AL- Cyelakh, All caregivers in the study of geriatric homes was married, with barely sufficient income .The study shows that,(90%), (70%) of caregivers in all geriatric care homes have (1-10) year of experiences respectively,(80%) of caregivers in geriatric home answers that they have emergency cases at their work time, (85%) of the emergency cases was saved in all geriatric care homes. Conclusions: The researcher recommends to increase training courses inside and outside Iraq and encourage employees to use safety measures to avoid injuries of the elderly, and prepare the advanced medical facilities to promote saving lives. As well as a medical test and evaluation of all elderly in geriatric care home to identify their health problems which lead to emergencies.